Pengaruh Persepsi Guru Tentang Budaya Sekolah dan Gaya Kepemimpinan Digital terhadap Perilaku Kerja Inovatif Guru di Sekolah XYZ Manado - Tanan, Dalpin; Purbojo, Rijanto (Kelola: Jurnal Manajemen Pendidikan, 2025)
Conducive school culture and digital leadership are essential in fostering teachers' innovative behavior in schools. The relation between these needs to be carefully observed in educational institutions. The aim of this research is to determine the influence of teachers' perspectives on school culture and digital leadership on teachers' innovative work behavior at XYZ Manado school. This research uses a quantitative correlation method to measure the influence of the studied variables. Data collection was carried out by distributing questionnaires to 63 teachers. This research uses the PLS-SEM model for hypothesis testing. Data validation is conducted through measurement validation, reliability testing, and structural model validation. The research results show that school culture has a positive and significant effect on teachers' innovative work behavior. Digital leadership does not have a positive and significant effect on teachers' innovative work behavior. Future research can examine the influence of school culture perception in various contexts, such as urban and rural areas.